Food journeys of a lifetime : 500 extraordinary places to eat around the globe (National Geographic Society, 2009)
Provides detailed, practical travel information to help make your dream food pilgrimage a reality--from building pastrami sandwiches in one of New York's bustling delicatessens to learning to cook delicious Chinese dumplings in Beijing or munching on hand-picked apples amid Vermont's fall foliage. Features recipes you can try at home.